2015
DOI: 10.1007/s00277-015-2538-1
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab-induced hand-foot syndrome in a Hodgkin lymphoma patient

Abstract: Dear Editor, Hodgkin's lymphoma accounts for approximately 30 % of all lymphomas. It is a highly curable condition with a 5-year survival above 85 %, which is even higher in patients with a limited stage disease [1]. Hodgkin's lymphoma (HL) that has relapsed after or is refractory to an autologous bone marrow transplant presents an ongoing treatment challenge [2]. Brentuximab vedotin (SGN-35) is an antibody-drug conjugate directed against the CD30 antigen expressed on HL. SGN-35 is usually well-tolerated but c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Infrequently, authors have documented TEN and DRESS syndrome with anti‐CD30 mAb use 116,200 . Table 3 lists the types of dermatologic toxicities seen with mAbs targeting CD30, including reports of the clinical aspects of dermatologic toxicities to those listed 127 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrequently, authors have documented TEN and DRESS syndrome with anti‐CD30 mAb use 116,200 . Table 3 lists the types of dermatologic toxicities seen with mAbs targeting CD30, including reports of the clinical aspects of dermatologic toxicities to those listed 127 …”
Section: Resultsmentioning
confidence: 99%
“…116,200 Table 3 lists the types of dermatologic toxicities seen with mAbs targeting CD30, including reports of the clinical aspects of dermatologic toxicities to those listed. 127…”
Section: Cd30mentioning
confidence: 99%
“…The efficacy of BV relies on its internalization into target cells, trafficking to lysosomes, and cleavage of cytotoxic MMAE from its conjugate monoclonal antibody by cysteine proteases; 5 therefore, a proposed mechanism for brentuximab-induced HFS is overaccumulation of cytotoxic MMAE in palmar and acral skin due to increased cleavage by lysosomal cysteine proteases. A literature review produced one reported case of HFS in a patient with Hodgkin lymphoma after a second infusion of BV, 6 and a single reported case of grade 2 HFS in a patient with Sézary syndrome during BV therapy. 7 …”
Section: Discussionmentioning
confidence: 99%